Peran Lingkungan Teman Dalam Menangani Kenakalan Siswa Di SMA Negeri 1 Muncar - Maghfiroh, Khusnul; Febiyanti, Olivia Dwi; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Delinquency committed by teenagers is behavior that is detrimental to themselves and to others. Juvenile delinquency for malicious behavior or juvenile delinquency is a socially pathological term that refers to a wide range, from socially unacceptable behavior to status violations to criminal acts. this is due to the influence of peers, because the influence of the school environment is very easy to influence the development of students, who are initially curious, then want to try and in the end are addicted to truancy, smoking or consuming liquor. The role of friends is needed in helping to deal with juvenile delinquency which can disturb the school environment. The purpose of providing motivation is so that teenagers who often commit deviant acts can change and become better individuals. From the results of our research, we conducted research on juvenile delinquency cases at SMA NEGERI 1 MUNCAR, namely students who skipped school hours and during Duha prayers, smoked, and consumed alcohol.